Novel spectrometers for environmental dose rate monitoring. (July 2018) - Kessler, P.; Behnke, B.; Dabrowski, R.; Dombrowski, H.; Röttger, A.; Neumaier, S.
Abstract: A new generation of dosemeters, based on the scintillators LaBr3, CeBr3 and SrI2, read out with conventional photomultipliers, to be used in the field of environmental gamma-radiation monitoring, was investigated. The main features of these new instruments and especially their outdoor performance, studied by long-term investigations under real weather conditions, are presented. The systems were tested at the reference sites for environmental radiation of the Physikalisch-Technische Bundesanstalt. The measurements are compared with that of well characterized classical dose rate reference instruments to demonstrate the suitability of new spectrometers for environmental dose rate monitoring even in adverse weather conditions. Their potential to replace the (mainly Geiger Müller based) dose rate meters operated in about 5000 European early waning network stations as well as in environmental radiation monitoring in general is shown. Highlights: A new generation of dosemeters, based on the scintillators was investigated. Their suitability for environmental dose rate monitoring is demonstrated. Their potential to replace dose rate meters is shown. With an adopted evaluation software they can have almost ideal dosimetric properties.